Oud neg.nr. 74199A-74213. 'Studieconferentie "De kwetsbaarheid van ons levenspatroon", H.P.S., Dellenhove' - Haas, Joh. de,
Oud neg.nr. 74199A-74213. 'Studieconferentie "De kwetsbaarheid van ons levenspatroon", H.P.S., Dellenhove'.